Indigenous Peoples and Climate Justice: Advisory Opinion 32/25 of the INTER-American Court of Human Rights and the Opinion of the International Court of Justice on the Obligations of States in relation to Climate Change - Iglesias, Maria del Angel (The Age of Human Rights Journal, 2025)
This paper explores how two 2025 Advisory Opinions, the Inter-American Court of Human Rights’ OC-32/25 and the International Court of Justice’s opinion on climate change, address indigenous peoples’ rights. Both recognise climate change as an existential threat but adopt contrasting approaches. The ICJ portrays indigenous peoples as vulnerable communities, without differentiated standards. Conversely, the IACtHR promotes a pro persona perspective, incorporating environmental democracy into its climate reasoning, recognising eco-anxiety, and equating indigenous knowledge with scientific evidence. Through comparative and critical analysis, this paper argues that while the ICJ reinforces universal obligations, the Inter-American Opinion operationalises them, providing stronger protection for indigenous identity and territorial rights.